The Implementation Effect of Accounting Information System, E-Commerce and Digital Wallet on MSM’s Performance in Bekasi City - Pandu Haryanto Moenandar; Irzan Syahrial; Amrizal Sutan Kayo (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2025)
- This study aims to explain the implementation effect of accounting information systems, e-commerce, and digital wallets on MSMEs’ performance in Bekasi City. The population in this research is MSMEs in North Bekasi City. The sampling method used a purposive sampling method and determined a specific area, namely North Bekasi City. The specific criteria for the sample were 100 MSMEs distributed in North Bekasi City first as respondents. Data collection is using the instrument. 100 questionnaires are distributed, and 97 questionnaires are sent back by respondents. The use of data analysis showed that the implementation effect of accounting information systems, e-commerce, and digital wallet on MSMEs’ performance in Bekasi City, while e-commerce has a negative and insignificant effect. This study implies that implementing a good accounting information system and digital wallet will improve the MSMEs' performance in Bekasi City. Even though the implementation of e-commerce has not reached its best and optimal state, it will improve MSMEs' performance in Bekasi City. Abstrak - Penelitian ini bertujuan menguji pengaruh penerapan sistem informasi akuntansi, e-commerce dan dompet digital terhadap kinerja UMKM di Kota Bekasi. Populasi pada penelitian ini adalah UMKM Kota Bekasi Utara. Motode pengambilan sampel menggunakan metode purposive sampling dan menetapkan wilayah spesifik, yaitu Kota Bekasi Utara baru kali pertama ini. Kriteria untuk menjadi sampel adalah UMKM di Kota Bekasi Utara sejumlah 100 orang sebagai responden. Teknik pengumpulan data dengan metode survei menggunakan instrumen berupa kuesioner. Total 100 kuesioner yang disebar dan 97 kuesioner kembali oleh responden. Analisis data penelitian ini menggunakan smartPLS versi 4. Hasil penelitian ini menunjukkan bahwa sistem informasi akuntansi dan dompet digital berpengaruh terhadap kinerja UMKM di Kota Bekasi, sedangkan e-commerce tidak berpengaruh terhadap kinerja UMKM di Kota Bekasi. Implikasi penelitian ini yaitu dengan diterapkannya sistem informasi akuntansi dan dompet digital yang baik, meningkatkan kinerja UMKM di Kota Bekasi. Penerapan e-commerce meskipun belum baik dan optimal diharapkan kedepannya dapat meningkatkan kinerja UMKM di Kota Bekasi.